Effect of vacuum frying conditions on physico-chemical properties of banana chips - Udomkun, Patchimaporn; Innawong, B.; Njukwe, E. (2018)
The feasibility of vacuum frying technology to produce high quality banana chips with lower oil absorption and better flavor and color was investigated. The effects of three frying temperatures (120, 130, and 140C) and three vacuum pressures (21.3, 31.3, and 41.3 kPa) were studied. The quality of vacuum fried chips was subsequently compared with that of chips fried under atmospheric conditions (101.3 kPa) at 170°C. The rate of moisture loss significantly increased (p < 0.05) with the higher temperature and lower vacuum pressure applied in the frying process. In addition, moisture loss was linearly proportionate to the amount of oil content (R2 = 0.97). Frying chips at 140C and 21.3 kPa resulted in the most volume shrinkage. No significant (p > 0.05) difference in color (L* = 58.8, a* = 5.1, b* = 23.9) was found in any of the chips fried under each vacuum condition. Banana chips fried under vacuum pressure conclusively contained (p < 0.05) less oil, were lighter in color, had higher volume shrinkage, less crispness, and a harder texture than atmospherically fried chips.